The Effect of Family Harmony on Juvenile Delinquency at SMAN 3 Kupang Timur Class of 2019 - ratnasari megy oematan; Indra Y Kiling; M. K. P. Abdi Keraf (Universitas Nusa Cendana, 2022)
Juvenile delinquency is a negative behavior of young people ranging from behavior that is not accepted by society to criminal acts. One of the factors driving juvenile delinquency is family harmony which based on previous research found a relationship between family harmony and juvenile delinquency. This study aims to determine the effect of family harmony on adolescents in SMA N 3 Kupang Timur students in June-July 2021. This study uses a quantitative method with a sample of 32 high school students. Data were analyzed using simple regression analysis. The results of this study found that there was an influence of the variable of family harmony with juvenile delinquency (p-value = 0.000). Meanwhile, the average family harmony score is in the low category (74.31), the average juvenile delinquency score is in the sufficient category (85.00). The conclusion in this study is that there is an influence between family harmony and juvenile delinquency. Keywords: Juvenile delinquency, family harmony